Convenient chemoenzymatic synthesis of (1S,7aS)-1-hydroxy-5-oxo-4-(2 `-carboxyethyl)-7a-methyltetrahydro-indane - a key intermediate of steroids - Kalkote, Uttam R.; Purude, A. N.; Puranik, Vedavati G.; Gurjar, M. K. (Journal of Molecular Catalysis B-Enzymatic, 2006)
A porcine pancreatic lipase mediated enzymatic hydrolysis of (+/-)-1-acetoxy-5-oxo-4-(2 `-carbomethoxyethyl)-7a-methyltetrahydroindane (5b) furnished (1S,7aS)-1-acetoxy-5-oxo-4-(2 `-carbomethoxyethyl)-7a-methyltetrahydro-indane (9) and (1R,7aR)-1-hydroxy-5-oxo-4-(2 `-carbomethoxyethyl)-7a-methyltetrahydro-indane (8) with > 99% e.e. which on further chemical hydrolysis gave 1 and ent-1, key intermediates of steroids. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: chemoenzymatic method; Enzymatic hydrolysis; steroids; terpenoids

Convenient formal synthesis of (+/-)-paroxetine - Chavan, Subhash P.; Khobragade, Dushant A.; Pathak, Ashok B.; Kalkote, Uttam R. (Synthetic Communications, 2007)
A formal total synthesis of antidepressant (+/-)-paroxetine employing a solvent-free Heck reaction is disclosed.
Keywords: antidepressants; carbamate; electrophile; Heck reaction; piperidines

Convenient formal synthesis of (2S,3S)-3-hydroxy pipecolic acid - Chavan, Subhash P.; Harale, Kishor R.; Dumare, Nilesh B.; Kalkote, Uttam R. (Tetrahedron-Asymmetry, 2011)
A convenient synthesis of (2S,3S)-3-hydroxy pipecolic acid starting from inexpensive and easily available L-(+)-tartaric acid has been described. (C) 2011 Elsevier Ltd. All rights reserved.